Engineering of CD8+ T cells with an HIV-specific synthetic notch receptor to secrete broadly therapeutic antibodies for combining antiviral humoral and cellular immune responses - Lina Meng; Haichi Zhao; Shangkun Chang; Weiting Li; Yinghui Tian; Ruihong Wang; Libian Wang; Tiejun Gu; Jiaxin Wu; Bin Yu; Chu Wang; Xianghui Yu (mBio)
ABSTRACT The application of immunotherapeutic strategies, such as chimeric antigen receptor-T cells and broadly neutralizing antibodies (bNAbs), for the treatment of human immunodeficiency virus (HIV) infection is hindered by the latent reservoirs and viral escape. Achieving long-term control of viral load in the absence of antiretroviral therapy requires a combination approach utilizing these immunotherapeutic strategies. For this purpose, we developed novel anti-HIV-1 synthetic Notch (synNotch) receptor-T cells, termed CD4-17b-VN, which express both a bNAb (VRC01) and a bispecific T cell-engaging protein (N6-αCD3) with antigenic control. The synNotch receptor-expressing cells can sense the viral antigen presented on both HIV-1 particles and the surface of target cells. A human T cell line equipped with the CD4-17b-VN circuit could effectively control VRC01 and N6-αCD3 secretion upon sensitization, suppress the infection of diverse subtypes of HIV-1 strains, and mediate specific bypass cytotoxic activity against infected and latency-reactivated cells. Additionally, CD4-17b-VN CD8+ T cells exhibited long-lasting suppression of infected cells and stronger killing effect on latency-reactivated cells in vitro. Importantly, we demonstrated that the synNotch receptor did not increase susceptibility to HIV-1 infection in the engineered cells. Our study validates the concept of a synNotch platform-based T cell therapeutic approach that can deliver broadly therapeutic antibodies in an HIV-1 antigen-controlled manner, which may have important implications for the functional cure of AIDS.IMPORTANCEAdoptive transfer of effector T cells modified with a chimeric antigen receptor has been proposed as an applicable approach to treat human immunodeficiency virus (HIV) infection. The synNotch receptor (SNR) system serves as a versatile tool, enabling customized programming of input and output functions in mammalian cells. Herein, we report a novel synNotch platform-based approach for T cell engineering targeting both cell-free particles and infected cells by coupling antibody neutralization with cytotoxicity. Our findings demonstrate that the engineered CD4-17b SNR enables controllable production of functional anti-HIV-1 broadly neutralizing antibody and bispecific T cell-engaging protein upon recognition of the viral particle and cell surface antigens by the bifunctional synNotch-T cells. Human primary CD8+ T cells equipped with the bifunctional synNotch circuit CD4-17b-VN can effectively suppress long-term viral replication and reduce latency-reactivated cells in vitro, without the undesired risk of being infected by the virus, suggesting their potential candidacy for AIDS therapy with prospects for future clinical applications.